(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Nowadays, students spend more time inside, and their exposure to artificial light increases. This light regulates circadian rhythm, an essential element for improving the environment and providing better illumination. Nevertheless, inadequate artificial lighting settings with improper illumination spectrum and colour temperature may disturb the circadian rhythm and impact sleeping habits. Researchers need to examine artificial lighting sources based on light fundamentals in order to enhance sleep quality, particularly for individuals who keep lights on while sleeping. To improve sleep quality, researchers must analyse artificial lighting sources based on light fundamentals, and lighting product current. The study aims to optimise artificial lighting environments for individuals with sleep disorders, specifically targeting Universiti Sains Malaysia students’ sleep habits during university. It investigates whether light fundamentals affect psychological and scientific health aspects. A review of literature investigates appropriate artificial lighting for treating sleep disorders, with a focus on explaining the circadian rhythm and applying the right spectrum, offering important information. The researcher’s final argument asserts that the quality of sleep can be enhanced by proper lighting design, especially for those suffering from insomnia. Adequate lighting, with proper lux levels, can improve sleep by establishing a suitable atmosphere, leading to improved overall health and well-being.